2014
DOI: 10.1097/jto.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of V20, VS5, Pulmonary Fibrosis Score on Baseline Computed Tomography, and Patient Age Improves Prediction of Severe Radiation Pneumonitis After Concurrent Chemoradiotherapy for Locally Advanced Non–Small-Cell Lung Cancer

Abstract: V20, VS5, age, and PFS on baseline CT are independent and significant risk factors for occurrence of severe RP. Combining these factors may improve the predictability of severe RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 22 publications
10
96
4
Order By: Relevance
“…We did not see a significant univariable relation between LuRa and baseline density although the trend is in the expected direction (Spearman's R = À0.14, p = 0.114). Furthermore, Tsujino et al [16] recently found age as an independent risk factor for developing RP on a multivariable analysis in a study that also included pulmonary fibrosis score based on honeycombing and pulmonary emphysema score based on the extent of the low density areas in the peripheral lung on baseline CT.…”
Section: Discussionmentioning
confidence: 97%
“…We did not see a significant univariable relation between LuRa and baseline density although the trend is in the expected direction (Spearman's R = À0.14, p = 0.114). Furthermore, Tsujino et al [16] recently found age as an independent risk factor for developing RP on a multivariable analysis in a study that also included pulmonary fibrosis score based on honeycombing and pulmonary emphysema score based on the extent of the low density areas in the peripheral lung on baseline CT.…”
Section: Discussionmentioning
confidence: 97%
“…Severe RP (grade ≥ 4) was also more common in elderly patients, occurring in 1% of those <70 years, compared with 6% of elderly patients [7]. Another study found age (≥68 years) increased the risk of grade ≥ 3 RP and combining age with dosimetric factors and pulmonary fibrosis score improved the predictability of severe RP [6]. However, in a study of 576 patients by Jin et al, there was no difference in the incidence of grade ≥ 3 RP between patients ≤ 60 years and >60 years [10].…”
Section: Agementioning
confidence: 99%
“…22 Furthermore, Stenmark et al 23 suggested that combining the dosimetric factor MLD with inflammatory cytokines that included TGF-b1 and interleukin (IL)-8 improved the accuracy of RP prediction. In a previous study performed to identify a more accurate model for symptomatic RP, the patient's age and pulmonary fibrosis score, together with dosimetric factors, were collectively found to be more predictive than dosimetric factors alone.…”
Section: Discussionmentioning
confidence: 99%